PENGARUH JIWA KEWIRAUSAHAAN, LINGKUNGAN TEMAN SEBAYA, DAN KEPRIBADIAN PROAKTIF TERHADAP POLA PIKIR KEWIRAUSAHAAN PADA MAHASISWA STIE DWI SAKTI BATURAJA - Hidayatullah, Rahmat; Malini, Hema; Yunsepa, Yopi (KOLEGIAL, 2024)
The purpose of this research is to determine the influence of entrepreneurial spirit, peer environment, and proactive personality on the entrepreneurial mindset of STIE Dwi Sakti Baturaja students. The results of multiple linear regression obtained the equation Y = 1,294 + 0.201 X1 + 0.437 X2 + 0.305 X3. Based on the R value of the correlation coefficient obtained using the interpretation guideline table, it can be seen that R = 0.908 is in the position 0.800-1.000, so the relationship is stated to be very strong, while the r square figure (coefficient of determination) is 0.825 or 82.5%. This value shows that the contribution of all independent variables, namely Entrepreneurial Spirit (X1), Peer Environment (X2) and Proactive Personality (X3) is 82.5% to the dependent variable, namely Entrepreneurial Mindset (Y). Meanwhile, the remaining 17.5% was contributed by other factors not examined in this study. Partially or t-test, namely with the t-count value of the Entrepreneurial Spirit variable (X1) of 2.561 > ttable 1.995, meaning that there is an influence of the Entrepreneurial Spirit on the Entrepreneurial Mindset (Y) of STIE Dwi Sakti Baturaja students. In the peer environment variable (X2) tcount is 6.952 > ttable 1.995, meaning that there is an influence of Peer Environment on the Entrepreneurial Mindset (Y) of STIE Dwi Sakti Baturaja Students. Meanwhile, the t-count value of Proactive Personality (X3) is 4.648 > ttable 1.995, meaning that there is an influence of the Entrepreneurial Mindset (Y) of STIE Dwi Sakti Baturaja students. Simultaneously from the F test, it can be seen that the value of Fcount > Ftable (106,732 > 3.13) so the conclusion is that all variable (X2), and Proactive Personality (X3) on the Entrepreneurial Mindset (Y) of STIE Dwi Sakti Baturaja Students..